Cities, Autonomy, and Decentralization in Japan - Carola Hein , Philippe Pelletier (2006)
Japan is known as a country in which a potent central power reigns over a compliant pyramidal hierarchy. For planning this has meant strong centralized government control. Yet, examples of autonomy have always existed in the politics, society, and economy of Japan and thrive today in various forms, particularly in urban areas. Following the growth and subsequent collapse of the bubble economy in 1990, and in response to globalization, new trends toward local autonomy and political and economic decentralization are emerging that must be evaluated in the context of the larger socio-political system.